2015
DOI: 10.1111/jerd.12135
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of Four Adhesion Strategies in Posterior Restorations—18‐Month Results

Abstract: When used in ideal clinical conditions, the composition of current dentin adhesives may be more clinically relevant than their adhesion strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In fact, most short-term studies involving posterior restorations with self-etch adhesive systems report less extensive loss of marginal integrity than the current work 7,31,32) . However, the results presented here are consistent with those of the study implemented by Perdigão et al, in which the one step self-etch adhesives disclosed significantly worse marginal integrity, color matching, surface texture and occlusal function in relation to the two step etch-and-rinse system studied 33) .…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In fact, most short-term studies involving posterior restorations with self-etch adhesive systems report less extensive loss of marginal integrity than the current work 7,31,32) . However, the results presented here are consistent with those of the study implemented by Perdigão et al, in which the one step self-etch adhesives disclosed significantly worse marginal integrity, color matching, surface texture and occlusal function in relation to the two step etch-and-rinse system studied 33) .…”
Section: Discussionmentioning
confidence: 52%
“…Among the five adhesive systems used in the present study, OBFL and CSEB were selected for being considered gold standard 6) for enamel and dentin bonding procedures due to their excellent and consistent results in some clinical trials with two years of followup 7,11,19) . The remaining adhesives were chosen from a single manufacturer in order to test alternative adhesive application modes within etch-and-rinse and self-etch approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been no other clinical study that tested the four current adhesive systems in primary teeth whereas studies with these adhesive systems in permanent teeth have been reported [41, 42]. Delbons et al [41] reported no statistically significant differences among the four adhesive systems with respect to all parameters including retention, marginal adaptation, and staining.…”
Section: Discussionmentioning
confidence: 99%
“…Delbons et al [41] reported no statistically significant differences among the four adhesive systems with respect to all parameters including retention, marginal adaptation, and staining. In a recent systemic review and a meta-analysis, it was concluded that besides adhesive strategy (i.e., etch-and-rinse versus self-etch), the specific brand is also important as there is a wide variation in the performance of adhesive systems [43, 44].…”
Section: Discussionmentioning
confidence: 99%